Male and overconfident groups overinvest due to inflated perceived ability to beat the odds - Renerte, Baiba; Hausfeld, Jan; Twardawski, Torsten (Frontiers in Behavioral Economics, 2023)
Organizational decisions are often made by groups rather than individuals. Depending on the group composition, each member’s characteristics — like gender and motivated beliefs — can influence the final group investment decision. To capture this, we design two types of investment situations in a randomized controlled laboratory experiment — one with fixed chances of success and one with performance-dependent chances of success. This novel design entails the perceived ability to “beat the odds” of the investment and thus models real-life investment situations more accurately than standard lottery choice. Our results demonstrate the benefits of mixed group composition in terms of both gender and overconfidence: Groups with all men and/or all overconfident group members consistently overinvest when a possibility to “beat the odds” is present, but not in standard situations. We explore several channels for our results and find that (i) individual probability perception, (ii) leader responsibility allocation and (iii) spillover effects from priming show significant effects.